Gut microbiota in early pediatric multiple sclerosis: a case−control study. (13th May 2016) - Tremlett, H.; Fadrosh, D. W.; Faruqi, A. A.; Zhu, F.; Hart, J.; Roalstad, S.; Graves, J.; Lynch, S.; Waubant, E.
Abstract : Background and purpose: Alterations in the gut microbial community composition may be influential in neurological disease. Microbial community profiles were compared between early onset pediatric multiple sclerosis (MS) and control children similar for age and sex. Methods: Children ≤18 years old within 2 years of MS onset or controls without autoimmune disorders attending a University of California, San Francisco, USA, pediatric clinic were examined for fecal bacterial community composition and predicted function by 16S ribosomal RNA sequencing and phylogenetic reconstruction of unobserved states (PICRUSt) analysis. Associations between subject characteristics and the microbiota, including beta diversity and taxa abundance, were identified using non‐parametric tests, permutational multivariate analysis of variance and negative binomial regression. Results: Eighteen relapsing−remitting MS cases and 17 controls (mean age 13 years; range 4–18) were studied. Cases had a short disease duration (mean 11 months; range 2–24) and half were immunomodulatory drug (IMD) naïve. Whilst overall gut bacterial beta diversity was not significantly related to MS status, IMD exposure was (Canberra, P < 0.02). However, relative to controls, MS cases had a significant enrichment in relative abundance for members of the Desulfovibrionaceae ( Bilophila, Desulfovibrio and Christensenellaceae ) and depletion in Lachnospiraceae and Ruminococcaceae (all P and q < 0.000005). Microbial genes predicted as enriched in MS versus controls included those involved in glutathione metabolism (Mann−Whitney, P = 0.017), findings that were consistent regardless of IMD exposure. Conclusions: In recent onset pediatric MS, perturbations in the gut microbiome composition were observed, in parallel with predicted enrichment of metabolic pathways associated with neurodegeneration. Findings were suggestive of a pro‐inflammatory milieu.